COOLING SCAVENGE AIR OF MAIN MARINE ENGINE BY ABSORPTION LITHIUM BROMIDE CHILLER IN EQUATORIAL LATITUDES - Андрій Миколайович Радченко; Дмитро Вікторович Коновалов; Іван Володимирович Калініченко; Чен Нінь; Хан Баочен (Авіаційно-космічна техніка та технологія, 2020)
The efficiency of cooling the scavenge air of the main low-speed engine of the transport vessel during operation in the equatorial tropical latitudes is analyzed. The peculiarity of the tropical climate is the high relative humidity of the air at the same time its high temperatures and temperatures of seawater. The cooling of the scavenge air with an absorption lithium bromide chiller by transforming the scavenge air heat into the cold was investigated. With this, the potentially possible minimum temperature of the cooled air was determined considering the temperature of the cold water (coolant) from the absorption lithium bromide chiller and the temperature differences in the heat exchangers of the intermediate water circuit of cooling. Absorption lithium bromide chillers are characterized by high efficiency of transformation of waste heat into cold - high coefficients of performance. Circuit-design solution of three-stage cooling system of scavenging air of ship's main engine - in high-temperature (cogeneration) stage using the extracted heat of scavenging air to get cold with absorption chiller and traditional stage for cooling scavenge air by seawater and low-temperature cooling stage by absorption chiller. The effect of deeper cooling of the scavenge air was determined in comparison with the cooling of the scavenge air with seawater, taking into account the changing climatic conditions during the route of the vessel. It is shown that due to the high efficiency of heat transformation in absorption chillers (high coefficients of performance 0.7…0.8), there is a significant amount of excess heat of scavenging air over the heat required to cool it to 22 °C, which reaches almost half of the available scavenge air heat on the Shanghai-Singapore-Shanghai route. This reveals the possibility of additional cooling the inlet of the turbocharger of the engine with the achieving almost double fuel economy due to the cooling of all cycle air of the low-speed engine, including the air at the inlet.